Meningkatkan Kemampuan Guru dalam Menyusun Rencana Pelaksanaan Pembelajaran Melalui Workshop di SD Negeri 28/X Simpang Berbak - Suharja Suharja (Universitas Batanghari Jambi, 2020)
This research is a school action research that aims to improve the ability of teachers in developing learning implementation plans through workshops at 28 / X Public Elementary School Simpang Desa Academic Year 2019/2020. The Subject of This Research Are Teachers In 28 / X Simpang Desa Elementary School, Berbak District, Tanjung Jabung Timur Regency, Jambi Province. This school action research was carried out in two cycles, the results of the evaluation of conversions with the results of the implementation of the first cycle workshop. The conversion results stated that the research had not yet reached the target, it needed to be continued with cycle II. The results of observers in cycle II showed that all parts of the workshops in preparing the lesson plans had been going well, so that there were no more parts of the lesson plan development activities that needed to be improved. While the second cycle evaluation which was converted with the workshop implementation table said that the research had reached the target limit of the completeness criteria of the teacher's ability in preparing the lesson plan that was equal to 88.2 and an average increase in the results of the workshops for the preparation of the teacher's lesson plan was 64.2 at the initial condition of improvement to 67.6 in the first cycle, from 67.6 to 94.2 in the second series. From the comparison of the average preparation of the RPP it states that the workshop can improve the ability of teachers in preparing learning implementation plans through workshops in 28/X State Elementary School Simpang Desa Academic Year 2019/2020.